Antenna Protein Clustering In Vitro Unveiled by Fluorescence Correlation Spectroscopy - Crepin, Aurélie; Cunill-Semanat, Edel; Kuthanová Trsková, Eliška; Belgio, Erica; Kaňa, Radek (International journal of molecular sciences, 2021)
Antenna protein aggregation is one of the principal mechanisms considered effective in protecting phototrophs against high light damage. Commonly, it is induced, in vitro, by decreasing detergent concentration and pH of a solution of purified antennas; the resulting reduction in fluorescence emission is considered to be representative of non-photochemical quenching in vivo. However, little is known about the actual size and organization of antenna particles formed by this means, and hence the physiological relevance of this experimental approach is questionable. Here, a quasi-single molecule method, fluorescence correlation spectroscopy (FCS), was applied during in vitro quenching of LHCII trimers from higher plants for a parallel estimation of particle size, fluorescence, and antenna cluster homogeneity in a single measurement. FCS revealed that, below detergent critical micelle concentration, low pH promoted the formation of large protein oligomers of sizes up to micrometers, and therefore is apparently incompatible with thylakoid membranes. In contrast, LHCII clusters formed at high pH were smaller and homogenous, and yet still capable of efficient quenching. The results altogether set the physiological validity limits of in vitro quenching experiments. Our data also support the idea that the small, moderately quenching LHCII oligomers found at high pH could be relevant with respect to non-photochemical quenching in vivo.
Keywords: photosynthesis; proteinové agregáty; Protein Aggregates; světlosběrné proteinové komplexy; chlorofyl; fluorescenční spektrometrie; fotosystém II (proteinový komplex); fluorescence correlation spectroscopy; Light; Fluorescence; koncentrace vodíkových iontů; homeodoménový protein Antennapedia; Antennapedia Homeodomain Protein; Photosystem II Protein Complex; Thylakoids; non-photochemical quenching; antenna proteins; světlo; zeaxanthiny; fototrofní procesy; Phototrophic Processes; fluorescence; Cluster Analysis; fotosyntéza; Spectrometry, Fluorescence; Zeaxanthins; Light-Harvesting Protein Complexes; Hydrogen-Ion Concentration; Photosynthesis; Chlorophyll; photoprotection; protein oligomerization; tylakoidy; detergent critical micelle concentration; shluková analýza